2011
DOI: 10.5578/tt.2417
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of smoking behaviors of 2509 Turkish university students and its correlates: a cross-sectional study

Abstract: ÖZET 2509 Türk üniversite öğrencisinin sigara içme davranış ve ilintilerinin değerlendirilmesi: Kesitsel bir çalışma SUMMARYAssessment of smoking behaviors of 2509 Turkish university students and its correlates: a cross-sectional study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…45 Another study 2509 university students found that 45.9% were smokers. 46 Our finding here is very encouraging; since smoking is the most common CVD risk factor in Turkey, these non-smoking nursing students could be very effective positive role models.…”
Section: Discussionmentioning
confidence: 55%
“…45 Another study 2509 university students found that 45.9% were smokers. 46 Our finding here is very encouraging; since smoking is the most common CVD risk factor in Turkey, these non-smoking nursing students could be very effective positive role models.…”
Section: Discussionmentioning
confidence: 55%
“…University students living in low income countries and those with a wealthier family background were more likely current tobacco users that student from middle and high income countries and with a poorer family background. Previous studies found, however, that lower socioeconomic status (Rozi et al, 2007;Mergen et al, 2011;Thakur et al, 2013) was associated with current tobacco use, and pooled cross-sectional data from the Global Youth Tobacco Surveys (Li and Guindon, 2013) found that there is a positive association between gross domestic product and the odds of an adolescent person in a low-and middleincome country being a current smoker. It is possible that in this study in particular in low income countries, university students form a minority affluent group being influenced and pressured by modern lifestyles which may be associated with increased tobacco use.…”
Section: Discussionmentioning
confidence: 99%
“…Factors associated with current tobacco use have been identified, in part, as follows: i) sociodemographic factors such as being male (Sen and Basu, 2000;Peltzer, 2001;Sinha and Gupta, 2007), older age (Peltzer, 2001) and lower socioeconomic status (Rozi et al, 2007;Mergen et al, 2011;Thakur et al, 2013); ii) beliefs and risk awareness, the importance to health of not smoking was associated with smoking status (non-smoking versus smoking) (Peltzer, 2001;Steptoe et al, 2002); iii) Poor mental health (depression, anxiety) (Halperin et al, 2010;Saravanan and Heidhy, 2014) and substance use, including risky drinking (Halperin et al, 2010;Mergen et al 2011) and illicit drug use (El Ansari et al, 2012); iv) violence experience, including intimate partner violence (Caleyachetty et al, 2014) and reported abuse (Halperin et al, 2010), and v) obesity (El Ansari et al, 2012). The aim of this study was to determine the prevalence of tobacco use, beliefs and risk awareness and psychosocial correlates of tobacco use among university students in 24 low, middle and emerging economy countries.…”
Section: Introductionmentioning
confidence: 99%
“…In the developing countries, it is known that, particularly among young people, youth smoking rate increases day by day (Peto et al, 1992). Therefore, as a result of measures taken to prevent the usage of cigarette, especially in the developed countries, youth smoking rate began to fall (Doll et al, 1994;Mergen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%